The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1590/s0103-50532003000600017
|View full text |Cite
|
Sign up to set email alerts
|

Chemical transformation of abietic acid to new chiral derivatives

Abstract: Neste trabalho descrevemos as reações de transformações químicas do anel C do ácido abiético (1a) com o objetivo de gerar novos síntons quirais. A partir do intermediário ceto-aldeído 9, obtido através da reação de ozonólise do abietato de metila (1b), foram sintetizados derivados bicíclicos tais como 14, 15 e 16 e um novo diterpeno tetracíclico 4. Foram também sintetizados, a partir 17, novos derivados contendo esqueleto abeo-abietano [6,6,5] tais como 19 e 20.Chemical transformations of the C-ring abietic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…Syntheses of all enones discussed herein were accomplished using commercial abietic acid 1 (Scheme ) freshly purified by crystallization of its isoamylamine salt. The synthetic strategy for preparation of cisoid enones was based on the observations reported in the literature that the particular double bonds within a conjugated diene system in the abietic acid are susceptible to selective oxidations in which the second double bond remains unchanged . For our purposes, we adopted cis -hydroxylation of the C13C14 bond, which enabled preparation of 7-en-14-one systems and iodine–water oxidation suitable for preparation of 8(14)-en-7-one derivatives…”
Section: Resultssupporting
confidence: 81%
“…Syntheses of all enones discussed herein were accomplished using commercial abietic acid 1 (Scheme ) freshly purified by crystallization of its isoamylamine salt. The synthetic strategy for preparation of cisoid enones was based on the observations reported in the literature that the particular double bonds within a conjugated diene system in the abietic acid are susceptible to selective oxidations in which the second double bond remains unchanged . For our purposes, we adopted cis -hydroxylation of the C13C14 bond, which enabled preparation of 7-en-14-one systems and iodine–water oxidation suitable for preparation of 8(14)-en-7-one derivatives…”
Section: Resultssupporting
confidence: 81%
“…In the 1 H NMR spectrum (Table ), three tertiary [δ 1.00 (s, Me-18), 0.88 (s, Me-19), and 0.74 (s, Me-20)] and two secondary [δ 1.10 (6H, d, J = 7.0 Hz, Me-16 and Me-17)] methyls, two oxymethines [δ 3.26 (dd, J = 11.6, 3.8 Hz, H-3), 4.62 (br d, J = 8.2 Hz, H-14)], and one olefinic proton [δ 5.64 (br s, H-7)] were observed. Detailed 2D NMR (COSY, HSQC, and HMBC) spectroscopic analyses suggested that 1 is a rearranged 14(13→12)- abeo -abietane diterpenoid similar to the semisynthetic methyl 7α,8α-epoxy-14α-hydroxy-13-oxo-14(13→12)- abeo -abieta-18-oate . Unlike this known structure, compound 1 has an additional hydroxy group (δ H 3.26, δ C 79.2) at C-3, a methyl group (δ H 1.00, δ C 27.6) instead of a methoxycarbonyl group at C-18, and a Δ 7,8 double bond (δ H 5.64, δ C 116.9, 142.4) replacing the 7α,8α-epoxy ring, which were confirmed by the key correlations between Me-18/Me-19/H-5 and C-3, between H-6 and C-7/C-8, and between H-11/H-14 and C-8 in its HMBC spectrum (Figure ).…”
Section: Resultsmentioning
confidence: 98%
“…As shown in Scheme , a 13,14-seco-abietane structure i , generated from abieta-7,13-diene via an oxidative cleavage at Δ 13,14 , is probably the common precursor to compounds 1 , 2 , and 15 . An unusual [6,6,5]-tricyclic abietane scaffold could then be constructed by an intramolecular aldol reaction of i , resulting in the formation of a C-12–C-14 bond in 1 and 2 . On the other hand, the 14-norabietane 15 may be generated from the key intermediate i through a sequence of oxidation reactions followed by decarboxylization.…”
Section: Resultsmentioning
confidence: 99%
“…Aromatic abietane diterpenes formed by these transformations are interesting because they show a wide variety of remarkable biological activities with proven or potential pharmacological applications . Abietic acid has also been successfully used as a substrate in the synthesis of a structurally complex and diverse collection of small molecules, including other terpenes, utilized in a variety of biological screens . Therefore, the use of abietic acid in organic synthesis is advantageous despite the ease with which it undergoes self‐oxidation under aerial exposure …”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Abietic acid has also been successfully used as a substrate in the synthesis of a structurally complex and diverse collection of small molecules, including other terpenes, utilized in a variety of biological screens. 3,11,12 Therefore, the use of abietic acid in organic synthesis is advantageous despite the ease with which it undergoes self-oxidation under aerial exposure. 13 Just the possibility of directing the abietic acid reactions to the desired product, along with its virtually unlimited availability, caused that in our recent studies, we have found it as convenient starting material for the synthesis of model cis-enones needed for in-depth dichroic studies.…”
mentioning
confidence: 99%